Biosaccharification and ethanol production from spent seaweed biomass using marine bacteria and yeast. (May 2017) - Sudhakar, M.P.; Jegatheesan, A.; Poonam, C.; Perumal, K.; Arunkumar, K.
Abstract: In this study, fresh and different spent biomasses of agarophytes, alginophytes and seaweed industrial spent biomass were evaluated for ethanol production. Saccharification of spent biomass of seaweeds was carried out using two methods such as mild acid and/or marine bacterial consortia. Total carbohydrate was recorded maximum in the fresh seaweeds (30.71 ± 4.21 and 39.75 ± 3.25% DW in Gracilaria corticata and Sargassum wightii, respectively) than the spent seaweed biomass, whereas reducing sugar production was recorded maximum in the industrial spent samples (14.6 ± 0.57 and 15.27 ± 1.02 g/L in agar and alginate spent, respectively). The mild acid pretreatment followed by bacterial consortia recorded more sugar conversion and ethanol production than the samples directly subjected to bacterial saccharification. The isolated marine yeast Meyerozyma guilliermondii AY17KJ754141, produced maximum ethanol from spent biomass (2.74 and 1.72 g/L in Sargassum ilicifolium and Gracilaria corticata, respectively). The spent biomass from agar and alginate industry recorded maximum of 2.34 and 2.60 g/L of ethanol respectively through ABC saccharification and marine yeast fermentation. Hence, the spent residues from agar and alginate industries, and seaweed spent biomass generated in the laboratory after pigment extraction were considered to be a good source of biomass for ethanol production based on sugar content. Graphical abstract: Highlights: Industrial spent biomass used for bioethanol production. Marine bacteria and yeast isolated and sequenced. Saccharification of spent biomass using marine microorganisms. High conversion of polysaccharide by marine organisms. 2.74 g/L ethanol yield achieved.